SEARCH OF IDENTITY: A COMPARATIVE STUDY OF THE NOVELS OF MANJU KAPOOR AND BHARTI MUKHERJEE - Bashir Ahmad Sheikh; Bilal Ahmad Bhat (Galaxy International Interdisciplinary Research Journal, 2022)
The portrayal of women in various works by various writers varies. Manju Kapur and Bharati Mukherjee have created diverse facets of Indian culture and the contemporary situation. Their women characters have not been represented as enslaved people but as victims of society, male crimes, and cultural struggles; in countries like India, people consider her a Goddess or an icon of sacrifice rather than a regular human being. The Goddess has shown to be the finest at what she does but can’t express herself. In the end, a woman is physically, intellectually, and psychologically entangled and unable to appreciate God’s gift of life. She appears most fragile at first but eventually gains a strong feeling of freedom and a stubborn personality. The present paper will address various elements of the women in the works of Manju Kapur and Bharti Mukherjee. The female in both Indian and Western contexts caught in contrasting circumstances has been mirrored in their novels. The novelists stress the pain and difficulties that the female heroine faces. The work is concerned with comparative investigation. The feminist or women-centred approach is a crucial development in Indian English Literature, dealing with experience and circumstance from a feminist perspective. In the previous four decades, there has been a shift in the portrayal of female characters. Contemporary authors have evolved from the old viewpoint of self-sacrificing women to that of identity-seeking women, who are no longer portrayed as sad figures or victims.